Analysis of the Influence of Certified Wastewater Treatment Personnel Competence as an Effort to Meet Industrial Wastewater Quality Standard Requirements in Semarang City - Agung Budiarto; Mochamad Arief Budihardjo; Fuad Muhammad (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2026)
This research examines the effect of certified personnel competence in industrial wastewater treatment on the fulfillment of industrial wastewater quality standards in Semarang City, Indonesia. Amid rapid industrial expansion, ensuring environmental sustainability has become increasingly challenging, prompting regulatory requirements for operator certification. The study adopts a quantitative descriptive approach, gathering data from 26 key wastewater treatment operators (POPAL) in major manufacturing sectors through structured questionnaires, interviews, and direct field observation. Findings demonstrate that the majority of industries in Semarang have already appointed certified wastewater treatment personnel, with most respondents possessing a strong educational background and extensive experience. Results indicate that certified operators significantly improve industrial compliance with wastewater quality standards, particularly regarding key parameters such as Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solids (TSS). Certified personnel exhibit enhanced ability in identifying risks, operating and maintaining wastewater facilities, and implementing standard procedures, which directly translates into higher rates of regulatory compliance. However, the research also finds that certification alone is not a panacea; certain industries still face challenges due to outdated technology, insufficient management support, or a lack of continuous training. These factors may hinder optimal wastewater treatment, even when certified personnel are present. The study’s implications are twofold. Theoretically, it affirms the critical role of human resource competence in effective industrial environmental management. Practically, it encourages policymakers and industry leaders to prioritize ongoing professional development, technological upgrades, and supportive management systems, in addition to certification. Such efforts will further strengthen the effectiveness of certified operators and improve overall environmental compliance. In conclusion, certified personnel competence, when supported by proper institutional and technological resources, is a key driver for successful and sustainable industrial wastewater management in Semarang.